Sequential expression of new gene programs in inducer T-cell clones. - Freeman, G J (1983)
We have prepared a cDNA probe that detects genes that are rapidly and abundantly expressed after exposure of inducer T-lymphocyte clones to antigen or mitogen. All inducer cells tested express a characteristic set of new mRNA, and these mRNAs are not expressed after activation of other lymphocytes. This initial burst of mRNA synthesis is paralleled by synthesis and secretion of a family of polypeptides that mediate inducer cell activity, including T- and B-cell growth factors, interferon, and molecules that bind to antigen. Expression of this initial genetic program precedes mitosis and is replaced within 74 hr by a different genetic program, which may control further cell division. The action of these sequential sets of genetic programs defines two stages of the cell's differentiation and accounts for altered expression of the cell's immunological functions.